2018
DOI: 10.1038/s41598-017-19133-9
|View full text |Cite
|
Sign up to set email alerts
|

Placental Morphology Is Associated with Maternal Depressive Symptoms during Pregnancy and Toddler Psychiatric Problems

Abstract: Maternal depressive symptoms during pregnancy predict increased psychiatric problems in children. The underlying biological mechanisms remain unclear. Hence, we examined whether alterations in the morphology of 88 term placentas were associated with maternal depressive symptoms during pregnancy and psychiatric problems in 1.9–3.1-years old (Mean = 2.1 years) toddlers. Maternal depressive symptoms were rated biweekly during pregnancy with the Center of Epidemiological Studies Depression Scale (n = 86). Toddler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…85 Another PREDO study assessing placental morphology among 86 participants found less variation in placental villous barrier thickness of gamma-smooth muscle actin-negative villi in the placentas of antenatally depressed mothers, indicating reduced placental maturation, due to prenatal depression. This placental structural change predicted internalizing and total psychiatric problems in 60 toddlers 86 .…”
Section: Discussionmentioning
confidence: 86%
“…85 Another PREDO study assessing placental morphology among 86 participants found less variation in placental villous barrier thickness of gamma-smooth muscle actin-negative villi in the placentas of antenatally depressed mothers, indicating reduced placental maturation, due to prenatal depression. This placental structural change predicted internalizing and total psychiatric problems in 60 toddlers 86 .…”
Section: Discussionmentioning
confidence: 86%
“…This supports the DOHaD hypothesis, which suggests that prenatal exposure to environmental adversity such as maternal depression may “program” child neurodevelopment (Barker, ), possibly through its effects on brain development (Van den Bergh et al., ). Furthermore, maternal depressive symptoms during pregnancy are also associated with maternal biomarkers with offspring neurodevelopmental relevance, including polyunsaturated fatty acids (Lin et al., ), proinflammatory cytokines (Christian, Franco, Glaser, & Iams, ), thyroid hormones (Bunevicius et al., ), cortisol (Seth, Lewis, & Galbally, ), and placental morphology (Lahti‐Pulkkinen et al., ), and with elevated placental corticotrophin releasing hormone (Moog et al., ), and placental mRNA gene expression levels of glucocorticoid ( NR3C1 ) and mineralocorticoid ( NR3C2) receptors (Räikkönen et al., ; Reynolds et al., ). These findings suggest that the mechanisms are complex and may include structural and functional alterations at the materno‐placento‐fetal unit.…”
Section: Discussionmentioning
confidence: 99%
“…The placental proteins hCG and PLAP as well as angiogenic factors like sFlt-1 are products of the trophoblast 29,30 . In light of these findings and recent data on thickness variability of the materno-fetal exchange barrier after prenatal stress 31 , the villous trophoblast qualifies as a candidate source tissue of placental structural and functional sexual dimorphism. Villous trophoblast is a bi-layered epithelial tissue with a biologically unique apical syncytial layer 30,32 , the workhorse of materno-fetal transfer processes.…”
Section: Introductionmentioning
confidence: 78%